Peranan Kebudayaan dalam Pembangunan: Perspektif Antropologi - Widen, Kumpiady (Journal Ilmu Sosial, Politik dan Pemerintahan, 2024)
The occurrence of various social conflicts and environmental damage in Indonesia, especially in Central Kalimantan, is assumed to be due to the neglect of cultural values ​​and norms which should be a reference in all development planning and implementation. Management of development by referring to cultural values ​​and norms is in accordance with the mandate of the 1945 Constitution, Regional Autonomy, and the Concept of Dayak Traditional Law and Customs in Central Kalimantan. Objectively, implementing various development programs in community life requires first getting to know the community, especially traditional communities in remote rural areas in Indonesia. The reason is because each community group has its own potential for self-sufficiency which is based on its unique and special socio-cultural background. Therefore, the development programs introduced should be adapted to the needs and potential of each community.